A hybrid crowdsourcing incentive mechanism based on users' preference - Azizan, Aqilah; Aris, Hazleen (2017)
Due to its nature, the success of a crowdsourcing application strongly relies on the volume of users’ participation.Thus, crowdsourcing applications need elements that can motivate users to participate, such as incentives or rewards.In this paper, the development of a hybrid incentive mechanism that incorporated users’ preferences is described.Literature review was first performed to identify the types of incentive implemented in existing crowdsourcing applications.This was followed by a survey through online questionnaire distribution to a total of 55 crowdsourcing users to determine their preference with regard to the identified incentive types.The hybrid incentive mechanism included most of the preferred incentive types indicated by the respondents.For the purpose of evaluation, two versions of crowdsourcing application prototype were developed, one of which was embedded with the hybrid incentive mechanism.Results obtained showed that participants who used the prototype with the incentive mechanism were more active in terms of number and contributions.Users’ retention was also greater in prototype with embedded hybrid incentive mechanism.